Reading and communication skills after universal newborn screening for permanent childhood hearing impairment. Issue 4 (17th November 2008) - McCann, D C; Worsfold, S; Law, C M; Mullee, M; Petrou, S; Stevenson, J; Yuen, H M; Kennedy, C R
Abstract : Background: Birth in periods with universal newborn screening (UNS) for permanent childhood hearing impairment (PCHI) and early confirmation of PCHI have been associated with superior subsequent language ability in children with PCHI. However their effects on reading and communication skills have not been addressed in a population-based study. Methods: In a follow-up study of a large birth cohort in southern England, we measured reading by direct assessment and communication skills by parent report in 120 children with bilateral moderate, severe or profound PCHI aged 5.4–11.7 years, of whom 61 had been born in periods with UNS, and in a comparison group of 63 children with normal hearing. Results: Compared with birth during periods without UNS, birth during periods with UNS was associated with better reading scores (inter-group difference 0.39 SDs, 95% CI 0.02 to 0.76, p = 0.042) and communication skills scores (difference 0.51 SDs, 95% CI 0.06 to 0.95, p = 0.026). Compared with later confirmation, confirmation of PCHI by age 9 months was also associated with better reading (difference 0.51 SDs, 95% CI 0.15 to 0.87, p = 0.006) and communication skills (difference 0.56 SDs, 95% CI 0.12 to 1.00, p = 0.013). In the children with PCHI, reading, communication and language ability were highly correlated (r = 0.62–0.84, p<0.001). Conclusion: Birth during periods with UNS and early confirmation of PCHI predict better reading and communication abilities at primary school age. These benefits represent functional gains of sufficient magnitude to be important in children with PCHI.